Characteristics of spinal injury in professional golfers in South Korea: a nationwide cross-sectional study - Hong Jin Kim; Hyung Rae Lee; Seungyup Lee; Dong-Gune Chang; Jae Hyuk Yang (BMJ Open)
Objectives To determine the golf-related characteristics of spinal injuries among professional golfers in South Korea.Design Cross-sectional survey study.Setting Online survey in South Korea.Participants A total of 439 professional active golfers (226 males and 213 females) in South Korea completed our survey.Methods Data collected included experiences of cervical (C)-spine and thoracic and lumbar (T/L)-spine injuries, demographics and golf-related characteristics among Korean professional golfers. Logistic regression analysis was used to explore any potential factors of golf-related spinal injuries.Results A total of 33.7% (148 of 439) experienced total spine injury in professional active golfers, presenting 15.5% of C-spine injuries and 21.9% of T/L-spine injuries. Multivariate logistic regression analysis showed that left-handed (OR, 2.79; 95% CI, 1.20 to 6.47 compared with right-handed) and fingertips <5 cm apart (fair grade) in the shoulder reach flexibility (OR, 0.33; 95% CI, 0.16 to 0.69) significantly influenced spinal injuries. Several factors such as age, golf-career years and body mass index were associated with time to injury, symptom duration and disability of spine injuries including C-spine and T/L-spine injuries.Conclusions Nearly 33.7% of Korean professional active golfers have experienced golf-related spinal injuries. These injuries appear to make left-handed golfers more vulnerable; however, adequate flexibility may offer protection against such injuries, suggesting the need for tailored preventative strategies based on individual biomechanical profiles.